Annual report 2024: International Institute of Islamic Thought and Civilisation (ISTAC-IIUM) - Norman, Nurul Ain (ISTAC-IIUM Publications, 2026)
The year 2024 marked a pivotal chapter in the continuing evolution of the International Institute of Islamic Thought and Civilisation (ISTAC-IIUM). With visionary leadership and renewed strategic focus, the Institute advanced its mission as a global centre of excellence for Islamic scholarship, transdisciplinary research, and civilisational renewal, anchored in Tawhidic epistemology and the higher objectives of the Shariah. Guided by the wisdom of IIUM’s President, Tan Sri Samsudin Osman, and Rector, Emeritus Professor Datuk Dr. Osman Bakar, ISTAC reaffirmed its mandate to harmonise sacred tradition with contemporary relevance. This vision found expression in a robust research performance, including the securing of o research grants and the production of 39 scholarly works, comprising academic books, book chapters, and peer-reviewed articles. The Institute’s flagship journal, Al-Shajarah, published three issues, including a special volume on renewal and reform in Islamic thought and civilisation. As a dynamic hub of intellectual exchange, ISTAC hosted more than 25 flagship lectures, spanning the ISTAC-World Professorial Lecture Series (IWPL), ISTAC-Distinguished Scholar Lecture Series (IDSL), and Futures of Integration of Human Knowledge and Civilisational Development forums. The Institute also organised and co-hosted major high-level gatherings. These events reflected ISTAC’s commitment to confronting pressing global issues: theology, epistemology, ethics, civilisational identity, and human dignity through an integrative and spiritually anchored lens. Workshops led by eminent scholars such as Prof. Jasser Auda and Prof. Jamal Badi strengthened the Institute’s research culture, focusing on maqasid-based inquiry, critical thinking, and transdisciplinary design.